PENGEMBANGAN BAHAN AJAR IPA BERBASIS SETS PADA SISWA MTsN 1 KENDARI - Abdul Kadir (Institut Agama Islam Negeri Kendari, 2017)
This study aims to produce the valid SETS-based science teaching materials for the practical and effective use in improving student learning outcomes on environmental pollution materials. This research is Research and Development with pretest-posstest one group design implemented at VII class’ students of MTsN 1 Kendari in the second semester of academic year 2015/2016. The instruments of the study are valid and reliable observations, questionnaires and cognitive tests to obtain the required data. Meanwhile, the data analysis technique is using descriptive and inferential analysis after meeting the normality and homogeneity requirements test. The results indicate; 1) the results of the validity of the SETS-based science test materials by the material and media experts which are valid and highly feasible materials to use, 2) the product practicality test results in small and large group samples which include all aspects considered to be generally implemented as a whole, and 3) the product effectiveness test results obtained through the average test of student learning outcomes before and after treatment which is significantly different, meaning that students' learning outcomes after treatment is increase. While the response of students and teachers on teaching materials used both in small and large group samples are both very good and suitable to use as a learning material on environmental contamination material in MTsN 1 Kendari.